Internet of Things - Enabled visual analytics for linked maintenance and product lifecycle management - Emmanouilidis, Christos; Bertoncelj, L.; Bevilacqua, M.; Tedeschi, Stefano; Ruiz Carcel, Cristobal (Elsevier, 2018)
When closed loop product lifecycle management was first introduced, much effort focused on establishing ways to communicate data between different lifecycle phase activities. The concept of a smart product, able to communicate its own identity and status, had a key role to play to this end. Such a concept has further matured, benefiting from internet things-enabled product lifecycle management advancements. Product data exchanges can now be brought closer to the point of end use consumption, enabling users to become more proactive actors within the product lifecycle management process. This paper presents a conceptual approach and a pilot implementation of how this can be achieved by superimposing middle of life relevant product information to beginning of life product views, such as a 3D product CAD model. In this way, linked maintenance data and knowledge become visual features of a product design representation, facilitating a user’s understanding of middle-of life concepts, such as occurrence of failure modes. The proposed approach can be particularly useful when dealing with product data streams as a natural visual analytics add-in to closed loop product lifecycle management.
Keywords: Internet of Things; Visual Analytics; Maintenance; Product Lifecycle Management